A comparative study on the efficiency of various cathodes in reducing hexavalent chromium at low voltage. Issue 4 (3rd March 2021) - K., Boopathiraja; A., Vignesh; S., Sathish; G., Keerthiga; S., Samdavid
Abstract: Electroreduction of Cr (VI) ions in effluents to its less toxic Cr (III) ions is a simple and efficient water treatment technique. The present study aims at using graphite as an anode to reduce the metal ion pollution that occurs due to the dissolution of the metal anode in electrochemical reduction. Also, the efficiency of aluminum, stainless steel, and copper plates as cathodes in removing chromium (VI) ions in aqueous potassium dichromate solution is compared in the low potential range. The effect of cathode surface area and solution pH on chromium removal efficiency has been studied. Stainless steel and copper are shown to have similar to no change in removal efficiency and higher than aluminum. The maximum removal efficiency of approximately 72% is obtained with the copper cathode (5.5 cm × 1 cm) and 6 volts in acidic pH. For the same voltage, with an increase in surface area, removal efficiency decreases due to a decrease in current density. The experimental data are fitted best with pseudo‐first‐order kinetics, indicating the potential flux limits the reduction rate in the lower range of current density. Thermodynamic studies concluded the feasibility, spontaneity, and endothermic nature of the electroreduction process.